The Effect Of Organizational Support On Work Satisfaction In Regional Secretariat Employees In Pariaman District - Nika Saputra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Human resources are one of the resources that exist in a company besides other resources, for example capital, materials, machinery in the company, so that it becomes useful. For this reason, companies are beginning to strive to excel in such competitive competition by trying to create quality and presentative human resources. This study aims to provide evidence that to determine whether or not there is an influence of organizational support on the work satisfaction of the Regional Secretariat Staff in Pariaman Regency. Data collection is done by survey method with a questionnaire. The data analysis technique used in this study is descriptive and quantitative analysis. The data collected is primary and secondary data which can be classified as independent variables and dependent variables. Organizational Support (influence variable), and Job Satisfaction in Regional Secretariat Staff of Pariaman Regency (affected variable). Testing the hypothesis in this study using a simple linear regression test. Based on the results of the study, it is known that there is a positive and significant influence between organizational support for and Job Satisfaction in the Regional Secretariat Staff of Pariaman Regency, obtained by a calculation that is greater than the Ttable where 2.806> 2.015 with a significance of 0.007